Development of Thermostable Lyophilized Sabin Inactivated Poliovirus Vaccine - Shin, Woo-Jin (mBio, 2018)
As oral poliovirus vaccine (OPV) causes vaccine-associated paralytic poliomyelitis, the polio endgame strategy introduced by the Global Polio Eradication Initiative calls for a phased withdrawal of OPV and an introduction of inactivated poliovirus vaccine (IPV). The introduction of IPV creates challenges in maintaining the cold chain for vaccine storage and distribution. Recent advances in lyophilization have helped in finding a temperature-stable formulation for multiple vaccines; however, poliovirus vaccines have yet to capture a stable, safe formula for lyophilization. In addition, efficient in vitro methods for antigen measurement are needed for screening stable vaccine formulations. Here, we report size exclusion high-performance liquid chromatography (SE-HPLC) as a reliable means to identify the leading lyophilized formulation to generate thermostable Sabin inactivated poliovirus vaccine (sIPV). High-throughput screening and SE-HPLC determined the leading formulation, resulting in 95% D-antigen recovery and low residual moisture content of sIPV following lyophilization. Furthermore, the lyophilized sIPV remained stable after 4 weeks of incubation at ambient temperature and induced strong neutralizing antibodies and full protection of poliovirus receptor transgenic mice against the in vivo challenge of wild-type poliovirus. Overall, this report describes a novel means for the high-throughput evaluation of sIPV antigenicity and a thermostable lyophilized sIPV with in vivo vaccine potency.